Strategic Priorities for Physical Activity Surveillance in the United States. Issue 13 (1st October 2016) - Fulton, Janet E.; Carlson, Susan A.; Ainsworth, Barbara E.; Berrigan, David; Carlson, Cynthia; Dorn, Joan M.; Heath, Gregory W.; Kohl, Harold W.; Lee, I-Min; Lee, Sarah M.; Mâsse, Louise C.; Morrow, James R.; et al.
ABSTRACT: Purpose: Develop strategic priorities to guide future physical activity surveillance in the United States. Methods: The Centers for Disease Control and Prevention and the American College of Sports Medicine convened a scientific roundtable of physical activity and measurement experts. Participants summarized the current state of aerobic physical activity surveillance for adults, focusing on practice and research needs in three areas: 1) behavior, 2) human movement, and 3) community supports. Needs and challenges for each area were identified. At the conclusion of the meeting, experts identified one overarching strategy and five strategic priorities to guide future surveillance. Results: The identified overarching strategy was to develop a national plan for physical activity surveillance similar to the U.S. National Physical Activity Plan for promotion. The purpose of the plan would be to enhance coordination and collaboration within and between sectors, such as transportation and public health, and to address specific strategic priorities identified at the roundtable. These strategic priorities were used 1) to identify and prioritize physical activity constructs; 2) to assess the psychometric properties of instruments for physical activity surveillance; 3) to provide training and technical assistance for those collecting, analyzing, or interpreting surveillance data; 4) to explore accessing data from alternative sources; and 5) to improve communication, translation, and dissemination about estimates of physical activity from surveillance systems. Conclusion: This roundtable provided strategic priorities for physical activity surveillance in the United States. A first step is to develop a national plan for physical activity surveillance that would provide an operating framework from which to execute these priorities.